Zeus Hypsistos en Macédoine : la dynamique sociale d’un culte « nouveau » dans le contexte socio-culturel de l’Empire - Rizakis, Athanase D. (Tekmeria, 2022)
The cult of Zeus Hypsistos seems to have emerged first in Macedonia and then to have spread to the other eastern provinces of the Roman Empire. Indeed, it is in western and central Macedonia, the heart of the ancient kingdom, that we find a large number of sanctuaries devoted to Zeus Hypsistos, together with offerings and votive dedications of various types, some of which date back to the second century BCE. This cult is quite distinct from that of Theos Hypsistos, which –with the exception of the cosmopolitan city of Thessalonike– is effectively absent from Macedonia. It is to be noted that in Macedonia Zeus Hypsistos retained the traditional iconographic elements of Zeus Olympios and was represented either anthropomorphically, in a sacrificial pose, or through his symbols (eagle, bull). Nevertheless, the two cults were not identical. Zeus Hypsistos was not a substitute for the patron god of the Macedonian royal house, which had been suppressed by Rome, nor did he represent a metamorphosis of the ancient divinity, associated with novel religious practices. It is clear that the new cult maintained the Zeus tradition but combined this with new elements and features, which gradually lent a different profile and character to the cult of Zeus Hypsistos, adapted to the religious and cultural context of the Roman Empire.